2004
DOI: 10.1093/brain/awh221
|View full text |Cite
|
Sign up to set email alerts
|

Temporal lobectomy: long-term seizure outcome, late recurrence and risks for seizure recurrence

Abstract: There is little information available relevant to long-term seizure outcome after anterior temporal lobectomy, particularly at extended postoperative periods. The aim of this study was an in-depth examination of patterns of longitudinal outcome and potential risk factors for seizure recurrence after lobectomy, utilizing a large patient sample with long follow-up. Included were 325 patients who underwent anterior temporal lobectomy between 1978 and 1998 (mean follow-up 9.6 +/- 4.2 years). Retrospective data wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

44
422
7
25

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 488 publications
(498 citation statements)
references
References 31 publications
44
422
7
25
Order By: Relevance
“…Several other recent studies have reported similar findings of seizurefree, drug-free status in 22% to 42% of patients after temporal lobe resection. 1,[4][5][6][7]12) Differences in pathologies, surgical procedures, and AED reduction policies in these other studies can explain the differences in the reported rates of postoperative AED cessation.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Several other recent studies have reported similar findings of seizurefree, drug-free status in 22% to 42% of patients after temporal lobe resection. 1,[4][5][6][7]12) Differences in pathologies, surgical procedures, and AED reduction policies in these other studies can explain the differences in the reported rates of postoperative AED cessation.…”
Section: Discussionmentioning
confidence: 92%
“…Only a few studies have focused on the relationships between surgical procedures and the overall rate of seizure-free outcome without drugs. 1,7) The type of surgery (ATL, AHE, or lesionectomy) was not a predictive factor in patients with seizure recurrence after AED cessation. 1) Similarly, in our study, hippocampectomy was not a predictive factor if the focus was correctly identified.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Late seizures are milder in severity and lower in frequency,53, 54, 55 easier to control with AEDs,54 and more likely to “run down” than their earlier counterparts 54. Also, late seizure recurrences usually arise from the edge of the original resection in patients with normal preoperative brain MRI,55 nonspecific surgical pathology,53 or long epilepsy duration 43. This is in contrast to early recurrences, which usually localize to brain regions distant to the site of resection or to residual incompletely resected epileptic lesions, implicating a localization or resection challenge.…”
Section: Surgical Outcomesmentioning
confidence: 99%
“…No clinical predictors could a priori predict patients whose seizures will recur during AED reduction as opposed to those whose seizures will recur after complete AED discontinuation 63. Similarly, although low seizure frequency, lack of secondary generalization, unilateral preoperative EEG and MRI findings, and lack of need for invasive EEG recordings correlate with early seizure freedom after surgery for TLE,46, 53 only the presence of a specific pathological diagnosis predicts long‐term seizure freedom: 40% of patients with gliosis or nonspecific pathology were seizure free 10 years after TLE surgery in the one series that investigated early versus late outcomes independently, as opposed to 80% of those with a specific pathological abnormality 46. Overall, a lot remains to be understood about the determinants of cure (defined by seizure freedom off AEDs) or long‐term seizure remission after epilepsy surgery.…”
Section: Surgical Outcomesmentioning
confidence: 99%